2017
DOI: 10.1074/jbc.m116.760645
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory cross-talk determines the cellular levels of 53BP1 protein, a critical factor in DNA repair

Abstract: DNA oubletrand reaks (DSBs) severely disrupt DNA integrity. 53BP1 plays critical roles in determining DSB repair. Whereas the recruitment of 53BP1 to the DSB site is key for its function, recent evidence suggests that 53BP1's abundance also plays an important role in DSB repair because recruitment to damage sites will be influenced by protein availability. Initial evidence has pointed to three proteins, the ubiquitin-conjugating enzyme UbcH7, the cysteine protease cathepsin L (CTSL), and the nuclear structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Hence, NuMA does not regulate 53BP1 expression but may rather sequestrate 53BP1 in the absence of damage to keep this master DDR effector in check. We note that other studies have shown degradation of 53BP1 by the proteasome after DNA damage (60,61). This effect was not observed in U2OS or HMT-3522 S1 cells in our experimental conditions, possibly due to cell line-specific expression and compartmentalization of the protein.…”
Section: Resultssupporting
confidence: 55%
“…Hence, NuMA does not regulate 53BP1 expression but may rather sequestrate 53BP1 in the absence of damage to keep this master DDR effector in check. We note that other studies have shown degradation of 53BP1 by the proteasome after DNA damage (60,61). This effect was not observed in U2OS or HMT-3522 S1 cells in our experimental conditions, possibly due to cell line-specific expression and compartmentalization of the protein.…”
Section: Resultssupporting
confidence: 55%
“…The ability of 53BP1 to bind to H2AK15ub is also limited by phosphorylation or acetylation of key residues within the ubiquitin-dependent recruitment region (13,55,56). In addition to its recruitment, the stability of 53BP1 is also regulated by proteasome-mediated degradation dependent on the E2 enzyme, UBCH7 (57). UBCH7 activity is up-regulated upon replication stress, leading to increased degradation of 53BP1 and therefore higher levels of HR.…”
Section: Brca1 and 53bp1: A Key Regulatory Partnershipmentioning
confidence: 99%
“…Gibbs-Seymour et al [155] also documented that lamins A/C interact with the 53BP1 protein under normal physiological conditions; however, DNA damage weakens this protein-protein interaction. In this case, the 53BP1 protein is degraded in the 26S proteasome, but the depletion of the ubiquitin-conjugating enzyme UbcH7 restores the lamin A/C-53BP1 complex [159]. Interestingly, the lamin precursor pre-lamin A interferes with damaged chromatin [160].…”
Section: Introductionmentioning
confidence: 99%